Slovakia’s stagnation in catching up with more developed economies: macroeconomic and regional dimensions - Morvay, Karol; Lentner, Csaba; Horbulák, Zsolt (Public Finance Quarterly, 2025)
In the aftermath of the global financial crisis in 2009, a number of Central and Eastern European economies, including the Visegrad four, experienced a phase of slowing real convergence. Their ability to catch up with the performance of more advanced European economies has declined to varying degrees and for varying lengths of time. The Slovak economy is a special case, which has been particularly hard hit by the problem of slowing real convergence. This paper shows the specific features of the Slovak case in both the macroeconomic and regional dimensions. It also explains the range of causes of this phenomenon. These are primarily related to the underdevelopment of new drivers of productivity: the parameters of capital accumulation have deteriorated, investment in intellectual property assets, the parameters of hi-tech activities and research and development have lagged far behind. In the regional perspective, the slowdown at macro-level convergence has mainly been reflected in the deterioration of the position of the strongest regions, and thus the performance of Slovakia’s regions has paradoxically moved closer together. The analysis is in the nature of an explanatory case study that explains the peculiar trajectory of Slovakia and the deterioration of its position in the V4 group. In doing so, it analyses primarily data from national accounts and regional accounts.